German language needs in Danish companies - Vandermeeren, Sonja (HERMES - Journal of Language and Communication in Business, 2003)
The first section of my paper provides a definition of the need for foreign languages in the business context and catalogues types and indicators of this need. In the second section the methods that can be employed in needs analysis studies are presented. Section three provides illustrative material from a questionnaire-based pilot survey. Taking the case of German companies, I investigate their expectations with regard to linguistic and cultural adaptation by their Danish business partners. Contrary to expectation, knowledge of German culture is regarded as more useful than German language knowledge. The educational implications of the findings of needs analysis studies are then dealt with in the fourth section.